Neuroticism, extraversion, and emotion sensitivity in a nonclinical young adult sample - Lauren A. Rutter; Prabhvir Lakhan; Laura Germine (PLoS ONE, 2026)
Introduction Accurate recognition of others’ emotional facial expressions, referred to as emotion sensitivity (ES), is a central component of nonverbal communication. Previous research suggests that personality traits such as neuroticism and extraversion may shape nonverbal emotion decoding but findings have been mixed. The present study examined whether these traits predict performance on the Belmont Emotion Sensitivity Test (BEST), a task designed to measure subtle discrimination of anger, fear, and happiness while minimizing response bias. Method A sample of 289 college students completed self-report measures of neuroticism and extraversion, as well as the Belmont Emotion Sensitivity Test (BEST), which assesses the ability to discriminate subtle differences in facial expressions of fear, anger, and happiness. Depression, anxiety, and stress levels were also measured. Results Female participants reported higher levels of neuroticism ( t = 4.39, p < .001; d = .59) and extraversion ( t = 2.33, p = .02; d = .33) t han male participants. Neuroticism severity was positively correlated with depression, anxiety, and stress. Extraversion was negatively correlated with depression, anxiety, and stress (range of r s = .55−.68, p < .001). Multiple regressions showed that neither neuroticism nor extraversion significantly predicted ES scores for any emotion category. Discussion Although women reported higher levels of neuroticism and extraversion, these traits did not predict performance on a validated emotion sensitivity task. These findings suggest that, in this nonclinical young adult sample, neuroticism and extraversion were not robust predictors of performance on this measure of emotion sensitivity. Implications are discussed for theories linking personality, psychopathology, and nonverbal emotion perception.